Clinical commissioning of a new patient positioning system, SyncTraX FX4, for intracranial stereotactic radiotherapy. (1st October 2018) - Tanabe, Satoshi; Umetsu, Osamu; Sasage, Toshikazu; Utsunomiya, Satoru; Kuwabara, Ryota; Kuribayashi, Toshiki; Takatou, Hiromasa; Kawaguchi, Gen; Aoyama, Hidefumi
Abstract: Background & Aims: A new real‐time tracking radiotherapy (RTRT) system, the SyncTraX FX4 (Shimadzu, Kyoto, Japan), consisting of four X‐ray tubes and four ceiling‐mounted flat panel detectors (FPDs) combined with a linear accelerator, was installed at Uonuma Kikan Hospital (Niigata, Japan) for the first time worldwide. In addition to RTRT, the SyncTraX FX4 system enables bony structure‐based patient verification. Here we provide the first report of this system's clinical commissioning for intracranial stereotactic radiotherapy (SRT). Materials & Methods: A total of five tests were performed for the commissioning: evaluations of (1) the system's image quality; (2) the imaging and treatment coordinate coincidence; and (3) the localization accuracy of cone‐beam computed tomography (CBCT) and SyncTraX FX4; (4) the measurement of air kerma; (5) an end‐to‐end test. Results & Discussion: The tests revealed the following. (1) All image quality evaluation items satisfied each acceptable criterion in all FPDs. (2) The maximum offsets among the centers were ≤0.40 mm in all combinations of the FPD and X‐ray tubes (preset). (3) The isocenter localization discrepancies between CBCT and preset #3 in the SyncTraX FX4 system were 0.29 ± 0.084 mm for anterior‐posterior, −0.19 ± 0.13 mm for superior‐inferior, 0.076 ± 0.11 mm for left‐right, −0.11 ± 0.066° for rotation, −0.14 ± 0.064° for pitch, and 0.072±0.058° for roll direction. the Pearson's product‐moment correlation coefficient between the two systems was >0.98 in all directions. (4) The mean air kerma value for preset #3 was 0.11 ± 0.0002 mGy in predefined settings (80 kV, 200 mA, 50 msec). (5) For 16 combinations of gantry and couch angles, median offset value in all presets was 0.31 mm (range 0.14–0.57 mm). Conclusion: Our results demonstrate a competent performance of the SyncTraX FX4 system in terms of the localization accuracy for intracranial SRT.